The Use of Online Learning Science Materials in Guided Discovery to Enhance Student Independence - Pratiwi, Anisha Yuniar; Rusilowati, Ani; Eko Nugroho, Sunyoto (Educational Management, 2021)
This study aimed to enhance fourth-grade Elementary School students' science learning outcomes through the guided discovery learning model. The research design is a combination method with a sequential explanatory design. The research was conducted at SDN 01 Jagung, SDN 01 Karyomukti, SDN 01 Kaibahan, SDN 02 Kesesi, and SDIT Plus Mutiara Umat with the experimental class serving as the control, and SDN 01 Langensari, with the control class serving as the control. The validity results indicate that Cronbach's alpha is 0.799 with an r table of 0.396 indicating that the data is reliable. The significance values in the pretest and posttest normality tests for the experimental class were 0.125 and 0.194. Meanwhile, the control class's pretest and posttest scores were 0.642 and 0.374 on the Normality Test, indicating that the data were normally distributed. The homogeneity test had a significance level of 0.190, 0.820, 0.181, 0.000, and 0.177 in the experimental, control, and selected schools. According to the ANOVA test results, indicating differences in learning outcomes between students taught using the guided discovery model and students taught using the assignment model. The study concludes that the guided discovery learning model has the potential to improve online science learning outcomes.